Ginsenoside Rg5/Rk1 ameliorated sleep via regulating the GABAergic/serotoninergic signaling pathway in a rodent model. Issue 2 (13th February 2020) - Shao, Jingjing; Zheng, Xiaoyan; Qu, Linlin; Zhang, Hui; Yuan, Huifang; Hui, Junfeng; Mi, Yu; Ma, Pei; Fan, Daidi
Abstract : As the most common sleep disorder, insomnia seriously affects people's everyday lives. Abstract : As the most common sleep disorder, insomnia seriously affects people's everyday lives. Phytochemicals have been shown to have excellent sleep-promoting effects. Therefore, this study was designed to investigate whether Rg5 and Rk1 extracted from ginseng had sleep-promoting effects and to explore their potential mechanisms. The results showed that Rg5 and Rk1 could significantly lessen the locomotor activity of mice and promote the sleep quality index, including increasing the amount of sleep in a pentobarbital sodium experiment with a threshold dose. In parallel, Rg5 and Rk1 could significantly shorten the sleep latency of mice and prolong the sleep time of mice. Furthermore, Rg5 and Rk1 augmented the GABA/Glu ratio, up-regulating the expression of the GABAA receptor and the GABAB receptor, whereas the GABAA receptor antagonist picrotoxin could antagonize the sleep quality of Rg5/Rk1. In addition, 5-HTP, the precursor of 5-HT, could enhance the sleep effect of Rg5 and Rk1 in mice, and both Rg5 and Rk1 could up-regulate the expression of 5-HT1A. These results were also confirmed by the detection of GABA and 5-HT in mouse cecum content. In conclusion, ginsenoside Rg5/Rk1 can exert sedative and hypnotic effects by affecting the GABA nervous system and the serotonin nervous system.